Study on the effect of metal salts on chlorophyll pigment extraction from fresh Sauropus androgynus leaves - Ho Kim Ngan Cao; Thi Anh Dao Dong (Journal of Agriculture and Food Research, 2023)
Sauropus androgynus is a precious medicinal herb containing a lot of chlorophyll, used to create a characteristic green color for food products. In this study, chlorophyll was extracted from S. androgynus by stirring fresh grinded leaves at 500 rpm at room temperature for 25 min with a solvent of 40% ethanol and added different salts, such as NaCl, Na2CO3, ZnSO4 to compare stability over time. In parallel with this experiment, S. androgynus blanched with 1% NaCl solvent was added with distinct metal salts to compare the effect of blanching solvent on chlorophyll pigment content and stability. The results showed that under normal extraction conditions at room temperature within 25 min with the addition of 1% of Na2CO3 salt based on the dry matter of materials, the chlorophyll content reached the highest value of 1.351 ± 0.032 mg/g dry matter (d.m.). Samples are sealed, protected from light, and stored at room temperature for 54 days and 124 days at 4 °C, toward the application of food color.